Efektivitas Sarana Temu Kembali Informasi Pada Sistem Media Asset Management Dengan Tinjaun Recall dan Precision di PT. Surya Citra Media Tbk - Nabilah Nurhilmy Ariedi; Elnovani Lusiana; Fitri Perdana (Universitas Wijaya Kusuma Surabaya, 2023)
Purpose Research. In order to provide information about visual news shows needed by the News division staff at PT Surya Citra Media Tbk quickly, precisely, and relevant as needed, the Media Asset Management system which is a means of retrieving information in the News Library at PT Surya Citra Media Tbk, needs to be seen and measured in order to know its effectiveness and ideality in bringing together information that suits the needs. This study aims to determine the effectiveness of the Media Asset Management system in the News Library of PT Surya Citra Media Tbk. Method. The method used is a formative evaluation research method with a quantitative approach. The population in this study is the entire collection of news shows stored in the Backdrop category in 2022. The sampling technique used was purposive sampling. The research sample is 20 news keywords entered into the Media Asset Management system. This research uses Lancaster's Recall and Precision effectiveness theory. Analysis Data. The research data were analyzed using descriptive statistical analysis techniques Results. The results showed an average Recall calculation ratio of 0.45 or 45% and an average Precision calculation ratio of 0.89 or 89%. Based on the nominal Precision level, the Media Asset Management system falls into the third category with a high or effective Precision level. Based on the identification of the comparison between the average Recall and Precision ratios, the Media Asset Management system has not been categorized in an ideal condition with a ratio between the Recall and Precision ratios that are not equally large, namely (4: 9). Conclusions. The Media Asset Management system in the News Library of PT Surya Citra Media Tbk is classified as effective but not yet categorized as being in an ideal stage or condition. Keywords: Effectiveness; Media Asset Management; Precision; Recall